Astrobiological Implications of the Organic and Inorganic Cyanide Utilization by a Novel Antarctic Hyperthermophilic Pyrococcus Strain - Blamey-Alegria, J (Springer, 2024)
Organic and inorganic cyanides are widely distributed in nature, yet not much is known about the ability of microorganisms to use these compounds as a source of nitrogen and/or carbon at high temperatures (>80 °C). Here we studied the capacity of organic and inorganic cyanides to support growth of an hyperthermophilic Pyrococcus strain isolated from Deception Island, Antarctica. This microorganism was capable of growing with aromatic nitriles, aliphatic nitriles, heterocyclic nitriles, amino aromatic nitriles and inorganic cyanides as nitrogen and/or carbon source. This is the first report of an hyperthermophilic microorganism able to incorporate these compounds in its nitrogen and carbon metabolism. Based on enzymatic activity and genomic information, it is possibly that cells of this Pyrococcus strain growing with nitriles or cyanide, might use the carboxylic acid and/or the ammonia generated through the nitrilase enzymatic activity, as a carbon and/or nitrogen source respectively. This work expands the temperature range at which microorganisms can use organic and inorganic cyanides to growth, having important implications to understand microbial metabolisms that can support life on Earth and the possibility to support life elsewhere. © The Author(s), under exclusive licence to Springer Nature Japan KK, part of Springer Nature 2024.